2007
DOI: 10.2466/pr0.100.4.1129-1139
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Physical Activity and Alexithymia: Results from Swimmers' Discourse Analysis

Abstract: The aim of this study was to describe and understand the relationship of swimmers' practice intensity and alexithymia features in discourse. This study investigated psychological processes in two groups of male swimmers training at different intensities. The first group was composed of 10 Expert amateurs (M age = 19.5 yr., SD = 1.9), who were competing at the national or international level and trained 22 hours per week. The second group was composed of 10 Amateur swimmers (M age = 20.5 yr., SD = 1.4), who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The relationship between alexithymia and exercise addiction has been examined in different populations of exercisers, such as those attending fitness centers [24], swimmers [25], and sports university students [26]. Some research has suggested that the use of physical activity could be a means by which these individuals try to suppress their unmentalized emotional states, as a form of dissociation from painful experiences [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between alexithymia and exercise addiction has been examined in different populations of exercisers, such as those attending fitness centers [24], swimmers [25], and sports university students [26]. Some research has suggested that the use of physical activity could be a means by which these individuals try to suppress their unmentalized emotional states, as a form of dissociation from painful experiences [17,24].…”
Section: Introductionmentioning
confidence: 99%
“…We report, for example, the work of Allegre et al (2007) who detect, from the analysis of verbal behaviour which concerns both the meaning of the expressions used and the expressed emotions, the presence of more pronounced alexithymic characteristics in amateur expert swimmers, who spend 22 hours a week training, compared with amateur swimmers who train 6 hours a week. The presence of alexithymia has also been detected in individuals addicted to skydiving: Woodman, Cazenave, Le Scanff (2008) have pointed out how skydiving represents an effective means for alexithymic women to regulate emotions.…”
Section: Sport Activities and Alexithymiamentioning
confidence: 99%
“…The risk of burnout in athletes is related to the intensity of training. The studies by Zekioglu et al [ 34 ] and Allegre et al [ 35 ], show that alexithymic athletes train more intensely.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it is known that, in young athletes, high-intensity training can cause emotional problems, injuries, anorexia, and a disruption of the relationship with others [ 56 ]. The studies of Zekioglu et al [ 34 ] and Allegre et al [ 35 ], underline the association between the athlete’s alexithymia and the practice of more intense training, which would be the origin of the burnout. Alexithymic athletes would be more at risk to develop burnout, so we can question the notion of limits in alexithymic athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation